SOSIALISASI NILAI KARAKTER SISWA SEKOLAH DASAR DAN MENENGAH MELALUI OLAHRAGA KARATE DI KABUPATEN KULON PROGO - Candra Widyastuti; Galih Dewanti; Erlina Erlina; Ari Septiyanto (GANESHA: Jurnal Pengabdian Masyarakat, 2025)
Sports are one of the fields that play an important role in character building in students. In the midst of the character crisis in students in this modern era, there needs to be an action that can have a positive impact on character building. The Department of Sports and Health is one of the departments in the Faculty of Vocational Studies, Yogyakarta State University, which opened the Sports and Health Laboratory (LABORKES). The Laboratory is a place for the community and elementary and secondary school students in the Serut and Terbah Village areas to participate in sports activities from various sports provided. There are many reasons for choosing this health laboratory, including having various adequate supporting facilities. Adequate facilities and in accordance with standards are one of the success factors in fostering character values ??and affective values ??in students. In this case, with the hope that the local community and study programs can collaborate and contribute to advancing the sports and health laboratory. The results of the study showed that students after participating in the socialization could develop karate sports talents and skills by demonstrating good discipline character values